Paleo-Mesoproterozoic arc-accretion along the southwestern margin of the Amazonian craton: The Juruena accretionary orogen and possible implications for Columbia supercontinent. (January 2017) - Scandolara, J.E.; Correa, R.T.; Fuck, R.A.; Souza, V.S.; Rodrigues, J.B.; Ribeiro, P.S.E.; Frasca, A.A.S.; Saboia, A.M.; Lacerda Filho, J.V.
Abstract: The southwestern portion of the Amazonian craton, between the Ventuari-Tapajós province and the Andean chain, has been ascribed to a succession of orogenic events from 1.81 to 0.95 Ga, culminating with widespread anorogenic magmatism. Southwestward of the Serra do Cachimbo graben occurs the Juruena accretionary orogenic belt (ca. 1.81–1.51 Ga), previously included in the Rio Negro-Juruena and Rondonian/San Ignácio geocronological provinces or Rondônia-Juruena geologic province. The Juruena orogen proposed here includes the Jamari and Juruena tectonostratigraphic terranes, products of convergence which culminated in the soft collision of the Paraguá protocraton and the Tapajós-Parima arc system (Tapajós Province) ca. 1.69–1.63 Ga ago. Geophysical, geochemical, petrological and geochronological data and systematic geological mapping suggest that the convergent event resulted in a single orogenic system with two continental margin arcs, namely the Jamari and Juruena arcs. Modern geological and tectonic approaches, combined with aerogeophysics data, enable to interpreting this wide region of the Amazonian craton as a Paleoproterozoic orogen with well defined petrotectonic units and tectonoestructural framework. The Juruena orogen is an E-W trending belt, about 1100 km long and 350 km wide, inflecting to NW-SE, in Mato Grosso, Amazonas and Rondonia, Brazil. The general direction of the belt, its inflections and internal geometric and kinematic aspects of its macrostructures do not corroborate the general NW-SE trend of the originally proposed geocronological provinces. The Juruena accretionary orogen has been the site of repeated reactivation with renewed basin formation, magmatism and orogeny during the Mesoproterozoic and the early Neoproterozoic. U-Pb and whole-rock Sm-Nd ages, Ar-Ar and Rb-Sr mineral ages suggest that the older high grade tectonometamorphic events in the Juruena accretionary orogen took place between 1.69 and 1.63 Ga, defining the metamorphic peak of the Rio Negro-Juruena orogeny and the original structural architecture of the orogen. The main structures of the Rio Negro-Juruena orogeny were almost completely obliterated between 1.42 and 1.37 Ga, due to the superimposed Rondonian-San Ignácio orogeny. Later on, between 1.20 and 1.12 Ga, these structures were affected by a ductile event represented by the large Ji-Paraná transpressive shear system and by the Tarilândia transcurrent shear zone developed under low-T amphibolite facies conditions, both related to the Sunsás orogeny. The evolution of Jamari and Juruena terranes as a Paleoproterozoic/Mesoproterozoic orogen developed between 1.81 and 1.51 Ga and their thorough reworking in Mesoproterozoic times is instrumental to establishing the position of the Amazonian craton in the proposed Paleo-Mesoproterozoic Columbia (Nuna) supercontinent, as well as in the Rodinia reconstruction at the end of the Mesoproterozoic. Highlights: Juruena orogen took place in SW Amazonian craton between 1.81 and 1.51 Ga. Is a accretionary orogen with E-W trend about 1100 km long and 350 km wide. The orogen includes Jamari and Juruena terranes, products of long-lived convergence. The orogen has been the site of two orogenic reativation in the Mesoproterozoic. It is relevant to establish of the Amazonian craton in the Columbia supercontinent.